Solid state fermentation of rice straw using Pleurotus sajor caju - Mahamad Yusof, Noor Mahizah; Yaakub, Halimatun; Alimon, Abdul Razak (2011)
An 2 x 6 factorial design experiment was conducted to investigate the effect of duration of incubation (15 and 30 days) on the chemical composition of rice straw fermented with Pleurotus sajor caju (PSC) with different levels of spawn (1, 2, 3, 4 and 5 g). Fifteen (15) g dry matter of straw plus mineral solution were placed into 500ml conical flasks and incubated at 28°C under static conditions. At the end of the incubation period the straw was dried and analyzed for dry matter, ash, neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin and crude protein (CP). The results showed that incubating straw for 30 days showed significant decrease in NDF, ADF and lignin content compared to those incubated for 15 days. The crude protein content was also significantly (p<0.05) increased at 30 days incubation period.